Human security dimensions in Malaysia's foreign policy, 2000-2010 - Ida Syahrina binti Haji Shukor (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
This study attempts to bridge the entrenched domestic-international chasm in policy making by examining how Malaysia's domestic human security approach affected the state's behaviour in the international arena during the period of 2000 to 2010. It argues that Malaysia's domestic dimensions to human security brought about the formulation and practice of foreign policy outputs with emphasis on human security elements. This study focuses on four elements of human security, namely personal security, community security, political security and economic security. This focus is vital in the case of Malaysia, as the state practises its own human security approach with an emphasis on these four elements of human security. In examining the domestic domain, the study looks at Malaysian laws, policies and individual policymakers' approach to each human security element during the years 2000 to 2010. The study further investigates whether Malaysia's approach towards each human security element is reflected in four foreign policy outputs, namely the state's contributions to the UN's peace-keeping operations, involvement in regional and international human rights commissions, role in the resolution of regional conflicts and initiatives on counter-terrorism cooperation. The study gathered data from Malaysian domestic laws and policies on each of the four elements of human security as well as biographies, documented speeches, press statements and media interviews, and written records of parliamentary debates. The study also conducted semi-structured interviews with prominent Malaysian policy makers to establish their domestic and foreign policy orientations. The study finds that there exists a link between Malaysia's domestic approach to human security and its international policy orientation. Domestically, Malaysia's approach to human security is reliant on the coverage, implementation and enforcement of the laws and policies. However, the key to the protection of human security in Malaysia and the promotion of the concept in Malaysian foreign policy lies with respective prime ministers. Future studies can apply this framework to Malaysia's approach in post-2010 or to other developing states during a specific period of time.